2013
DOI: 10.1093/ndt/gft295
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea is associated with lower prevalence of albuminuria in adults with sickle cell disease

Abstract: In our population of sickle cell patients, those using hydroxyurea were less than one-third as likely to exhibit albuminuria. Hydroxyurea use may prevent development of overt nephropathy or the progression of sickle cell disease nephropathy to end-stage renal disease, and its use for this indication merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…As such, in SCD mice, HU therapy appears to restore alterations in unbalanced parameters of the RAS. To date there is no evidence regarding basal RAS parameters or the effects of HU on the RAS in human SCD, and while HU therapy has been suggested to have renoprotective effects in SCD, being associated with lower albuminuria and improved glomerular filtration, no significant effects of HU on blood pressure have been reported in these patients (Desai et al, 2012;Laurin et al,2014;Silva Junior et al, 2014). As such, while observations of an HU-induced augmentation in Ang II in mice could indicate a potentially deleterious effect of this drug in SCD, further studies in humans are required especially given that concurrent increases in HbF in humans on HU may modulate these effects.…”
Section: Discussionmentioning
confidence: 99%
“…As such, in SCD mice, HU therapy appears to restore alterations in unbalanced parameters of the RAS. To date there is no evidence regarding basal RAS parameters or the effects of HU on the RAS in human SCD, and while HU therapy has been suggested to have renoprotective effects in SCD, being associated with lower albuminuria and improved glomerular filtration, no significant effects of HU on blood pressure have been reported in these patients (Desai et al, 2012;Laurin et al,2014;Silva Junior et al, 2014). As such, while observations of an HU-induced augmentation in Ang II in mice could indicate a potentially deleterious effect of this drug in SCD, further studies in humans are required especially given that concurrent increases in HbF in humans on HU may modulate these effects.…”
Section: Discussionmentioning
confidence: 99%
“…A number of small-scale studies in adults with SCD have shown an association between HU use and a reduction in the presence and/or degree of proteinuria. 30 In case 2, HU treatment was associated with a stabilization in renal function that had been previously declining. Although these studies and anecdotal cases do not offer conclusive evidence that HU treatment prevents the progression of SCN to CKD directly, overall, HU should have a beneficial effect through reduction of frequency of VOCs that can precipitate AKI.…”
Section: Humentioning
confidence: 95%
“…Attenuation of hemoglobinuria was also demonstrated in multiple case reports including, during CPB in a patient with b-thalassemia, following autologous stem cell transfer post ablative treatment, during HELLP syndrome, ABO incompatibility transfusions and coil embolisation for patent ductus arteriosus [57][58][59][60][61]. A single German study also reported beneficial results in the attenuation of hemoglobinuria in a case of ABO incompatibility transfusion [43]. In the majority of cases, a dose to effect strategy was employed, usually monitoring the disappearance of overt hemoglobinuria.…”
Section: Evaluation Of the Hypothesis/ideamentioning
confidence: 92%
“…Hydroxyurea, which increases the concentration of fetal Hb, has been reported in the BABY HUG trials as beneficial in reducing the occurrence of acute chest syndrome, vaso-occlusive crises, required transfusions and hospitalizations in children [41,42]. Studies reporting the effect on micro-and macro-albuminuria have been less consistent [43,44]. Angiotensin converting enzyme inhibitor (ACEi), has been shown to decrease albuminuria in SCD [45].…”
Section: Evaluation Of the Hypothesis/ideamentioning
confidence: 99%